A novel flux splitting scheme with robustness and low dissipation for hypersonic heating prediction. (December 2018) - Chen, Shu-sheng; Yan, Chao; Zhong, Kang; Xue, Hai-chao; Li, Er-long
Highlights: A novel flux splitting scheme called AUPM is developed. This scheme is shock-stable and low-dissipation. It can exactly preserve contact discontinuity and eliminate numerical overshoots. It also avoids empirical parameters and has high resolution for low speed flows. Numerical results indicate its good application for hypersonic heating prediction. Abstract: In this paper, a novel flux splitting scheme is devised to overcome some difficulties in hypersonic heating prediction. Based on Zha-Bilgen splitting approach, the novel scheme integrates three key ingredients: (i) advection flux estimated by AUSM algorithm; (ii) pressure flux estimated by HLL algorithm; (iii) isentropic condition and low-Mach number fix applied in the difference diffusion term of pressure flux. Then, test problems are carefully selected for systematic assessment of the resulting scheme in terms of robustness and accuracy. The proposed scheme is shock-stable and low-dissipation; meanwhile it can exactly preserve contact discontinuity and eliminate numerical overshoots. A series of hypersonic viscous flow cases, such as 3D Mars Science Laboratory (MSL) reentry capsule, demonstrates its superior performance compared with existing upwind schemes, and is potentially a good candidate for hypersonic heating prediction.